Design and Construction of a Smart Monitoring and Phase Failure Protection Circuit in a Three-Phase Electrical Network - Haryogi Setyanto; KGS M Ismail; Agus Herianto (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
The three-phase electrical system at airports plays an important role in ensuring aviation safety and security, especially in the operation of three-phase loads at airports which must operate without interruption according to regulations. This research develops a three-phase phase failure monitoring and protection system based on the Internet of Things (IoT) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method to overcome the limitations of conventional monitoring which still relies on manual measuring instruments. This system was built using the NodeMCU ESP 8266 microcontroller to process data from the PZEM-004T sensor which measures voltage and current parameters. The data is transferred in real-time via a WiFi connection to the Blynk platform, with the performance monitoring tool reading the parameters for each phase, namely Phase R at 0.22%, Phase S: ??0.22%, Phase T: 0.22% and as follows. control when a phase disturbance occurs in one of the feeders, the tool is able to detect and cut off the electricity in less than 1 second. In addition, after the disturbance is resolved and the feeder condition returns to normal, the tool can quickly reconnect electricity in less than 5 seconds.